Advanced information systems engineering workshops : CAiSE 2015 International Workshops, Stockholm, Sweden, June 8-9, 2015, Proceedings /: CAiSE 2015 International Workshops, Stockholm, Sweden, June 8-9, 2015, Proceedings. (2015) - Unknown
No abstract available